Stereoselective Synthesis of Tetrahydrofuran Lignans - Soorukram, Darunee; Pohmakotr, Manat; Kuhakarn, Chutima; Reutrakul, Vichai (Synthesis, 2018)
This short review aims to summarize the reports on stereoselective synthesis of naturally occurring tetrahydrofuran lignans published during the period of 2006 to 2018. The stereoselective construction of non-natural tetrahydrofuran frameworks is not included in this review.1 Introduction2 Stereoselective Synthesis of 2,5-Diaryltetrahydrofuran (CL5-a)2.1 Synthesis of CL5-a via Friedel–Crafts Arylation or Nucleophilic Addition/Reduction of γ-Butyrolactones2.2 Synthesis of CL5-a via Intramolecular Cyclization of 1,4-Diarylbutanediols2.3 Synthesis of CL5-a via Diastereoselective Hydrogenation of Furan Derivatives2.4 Synthesis of CL5-a via Cycloaddition Reaction of Substituted Cyclopropane Derivatives3 Stereoselective Synthesis of 2-Aryl-4-benzyltetrahydrofuran (CL5-b)4 Stereoselective Synthesis of 3,4-Dibenzyltetrahydrofuran (CL5-c)5 Conclusions
Keywords: lignans; furans; stereoselective synthesis; bioactive compounds; natural products